ANALISIS TINGKAT KEPUASAN KONSUMEN ATAS KUALITAS PELAYANAN PADA SOLARIA RESTORAN MALL SKA DI KOTA PEKANBARU - Sri Rahmi Murni; Jusherm Jusherm; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to determine the level of customer satisfaction on the quality of service on Solaria Restaurant City Mall SKA Pekanbaru. The population in this study is that consumers who visit the Solaria Restaurants Mall SKA Pekanbaru. The determination of the amount of sample 98 people based on Hair et. al, convinience using sampling techniques. Analysis of the data in this study using Impertance Performance Analysis (IPA). The results of the study with an average of respondents' answers to the level of satisfaction on reability is with category of satisfied. Then variable respondent satisfaction level of responsiveness as satisfied. Furthermore, customer satisfaction with ansurance variable is satisfied. Customer satisfaction with empathy variable with the satisfied category. While customer satisfaction with tangible variables is categorized as very satisfied.Keywords : Customer Satisfaction, Quality of Service